GEHEP 010 study: Prevalence and distribution of hepatitis B virus genotypes in Spain (2000–2016). Issue 4 (October 2020) - Aguilera, Antonio; Trastoy, Rocío; Rodríguez-Frias, Francisco; Muñoz-Bellido, Juan Luis; Melón, Santiago; Suárez, Avelina; Orduña, Antonio; Viciana, Isabel; Bernal, Samuel; García-Bujalance, Silvia; Montiel, Natalia; Molina, José Manuel; et al.
Highlights: The distribution of HBV genotypes in Spain varies based on age, sex, and origin. HIV-coinfection, geography and epidemiology also affect HBV genotype distribution. Our findings are informative to work towards to the 2030 elimination goals. Summary: Objective: To study the prevalence and distribution of HBV genotypes in Spain for the period 2000–2016. Methods: Retrospective study recruiting 2559 patients from 17 hospitals. Distribution of HBV genotypes, as well as sex, age, geographical origin, mode of transmission, HDV-, HIV- and/or HCV-coinfection, and treatment were recorded. Results: 1924 chronically HBV native Spanish patients have been recruited. Median age was 54 years (IQR: 41–62), 69.6% male, 6.3% HIV-coinfected, 3.1% were HCV-coinfected, 1.7% HDV-co/superinfected. Genotype distribution was: 55.9% D, 33.5% A, 5.6% F, 0.8% G, and 1.9% other genotypes (E, B, H and C). HBV genotype A was closely associated with male sex, sexual transmission, and HIV-coinfection. In contrast, HBV genotype D was associated with female sex and vertical transmission. Different patterns of genotype distribution and diversity were found between different geographical regions. In addition, HBV epidemiological patterns are evolving in Spain, mainly because of immigration. Finally, similar overall rates of treatment success across all HBV genotypes were found. Conclusions: We present here the most recent data on molecular epidemiology of HBV in Spain (GEHEP010 Study). This study confirms that the HBV genotype distribution in Spain varies based on age, sex, origin, HIV-coinfection, geographical regions and epidemiological groups.